Public Policy and Biofuels: Energy, Environment and Food Trilemma - KALETNIK, Hryhorii; PRYSHLIAK, Viktor; PRYSHLIAK, Natalia (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
Current policies in energy sector address issues including environmentally friendly technologies, clean and renewable energy supplies and encourage more efficient energy use. The biofuel policy aims to promote production and consumption of fuels made from biomass. Despite the presence of both positive and negative effects of biofuels the world production and consumption of biofuels have been increasing significantly. To a large extent, this is due to an active public policy in the field of stimulating the production and consumption of biofuels. The volume of biofuel production in the leading countries (USA, Brazil and the EU) has been analyzed. The influence of public policy in the sphere of biofuel production and consumption on energy, environment and food security of the state has been examined. Multivariable and paired correlation as well as regression analysis aimed to determine the price dependence of the main crops used as feedstock for biofuels production, the volume of their production or processing for biofuels and the volumes of biofuel production have been carried out. As a result of this analysis the impact of the public policies in biofuels on the еnergy, environment and food security has been identified.